Disclosure of Greenhouse Gas Reduction Information and Its Impact on the Firm Value of Thai Listed Companies - Sriersan, Thanai; Rasrirattana, Thanadom; Panna, Ukrit (Parichart Journal, 2025)
This study examines the disclosure of greenhouse gas (GHG) reduction information and its impact on the firm value of Thai listed companies. This research focuses on promoting global environmental sustainability, particularly in economically developing regions. The researchers collected data from 113 on the Thai listed companies. The data were obtained specifically from companies that disclosed information on GHG emission reduction in the SETSMART database during the 2023 fiscal year. The data collection focused on disclosures related to GHG reduction, ESG score rankings, and corporate GHG reduction management plans, all of which may impact firm value, as measured by Tobin’s Q. The researchers employed multiple regression analysis. The study found that a high level of GHG disclosure positively influences ESG scores, which, in turn, enhances firm value. This research is beneficial for listed companies as it demonstrates that responsibility in reducing GHG emissions for environmental preservation can contribute to increased firm value. Additionally, the implementation of a GHG management plan helps support the disclosure of such information, contributing to the company’s sustainability.